The development of an interferon-gamma (IFNγ) assay for the diagnosis of tuberculosis in African elephants (Loxodonta africana) and black rhinoceros (Diceros bicornis) - Rutten, Victor P.M.G. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2003.